Directionality and polarity in recA protein-promoted branch migration. - Cox, M M (1981)
The recA protein of Escherichia coli promotes the complete exchange of strands between full-length linear duplex and single-stranded circular phi X174 DNA molecules. Analysis of the reaction by electron microscopy confirms that D loops containing short heteroduplex regions are rapidly formed at the ends of the linear duplex, followed by a relatively slow branch migration that converts the D loops to nicked circular duplexes (RFII) and displaced linear single strands. Heteroduplex extension and displacement of the linear single strand are concerted. Heterologous sequences within the linear duplex halt branch migration and lead to the accumulation of D loops. Although D loops can be formed at either end of the linear duplex, recA protein-promoted branch migration proceeds uniquely in the 3' leads to 5' direction relative to the (--) strand of the linear duplex.